IMPROVING STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT BY USING TEACHER’S SCAFFOLDING - Elda, Elda; Apriliaswati, Rahayu; Rezeki, Yanti Sri (Journal of English Education Program, 2022)
This classroom action research aimed to improve student’s reading comprehension of descriptive text by using the teacher’s scaffolding, especially in the aspect of vocabulary, finding the detailed information and main idea, determining pronoun reference, and using correct language features. This research was conducted in three cycles, with 32 students of the VII E class in SMP Negeri 03 Sungai Raya as the subject. The collected data were qualitative and quantitative data. The qualitative data were gathered from the observation checklist and field notes, and the quantitative data were collected from the reading test. The findings showed that the use of teacher’s scaffolding in teaching reading comprehension text was encouraged students to determine the language features and pronoun reference, completing the detailed information and main idea and, increasing students’ vocabulary. The students became more active, enthusiastic, motivated and, confident in the reading comprehension class. The students enjoyed reading descriptive text and followed the learning activities. Based on the quantitative data, the students’ score of cycle 1 was 65,59, increased to 78,84 in the second cycle and 83 in the third cycle.